MicroRNA-21 regulate the cell apoptosis and cell proliferation of polycystic ovary syndrome (PCOS) granulosa cells through target toll like receptor TLR8. Issue 1 (1st January 2021) - Yu, Yingying; Li, Guojing; He, Xiaoying; Lin, Yu; Chen, Zheng; Lin, Xianhua; Xu, Hong
ABSTRACT: Polycystic ovary syndrome (PCOS) is a complex reproductive endocrine disease characterized by polycystic ovary. The aim of the study was to assess microRNA-21 regulates granulosa cell apoptosis and proliferation in polycystic ovary syndrome through target toll-like receptor 8. Granulosa cells were collected from 30 PCOS patients and 30 normal patients with tubal or male factor infertility (control) during in vitro fertilization-Embryo Transfer (IVF-ET) and were flash frozen with liquid nitrogen for storage for subsequent use. PCOS diagnosis was based on the revised standards of the American Society of Reproductive Medicine (ASRM) and the Rotterdam criteria PCOS granulosa cells and control granulosa cells were cultured in DMEM/F12 medium containing 10% fetal bovine serum and 1% antibiotic. After this RT-PCR, Western blot assessment and Detection of apoptosis by flow cytometry were conducted. The results of qPCR showed that the mRNA and protein expression of TLR8 in PCOS granulosa cells were significantly increased compared with the normal group. The results of Western blot also showed that the expression of TLR8, IFN-γ, TNF-α and IL-12 gene protein in the transfected cells was significantly higher than that in the control cells. Here, we show that miR-21 and TLR8 significantly increased in PCOS granulosa cell as compared with normal granulosa cells, and miR-21 enhances the TLR8 mRNA translation and then promotes the IFN-γ, TNF-α, and IL-12 secretion. Our study demonstrates that miR-21/ TLR8 involved in the PCOS inflammation, it provides profound insights into pathogenesis of PCOS.